ENHANCED WEIGHT OPTIMIZED RECURRENT NEURAL NETWORKS BASED ON SINE COSINE ALGORITHM FOR WAVE HEIGHT PREDICTION - ALQUSHAIBI, ALAWI ALI ALI MANEA (2021)
Constructing offshore and coastal structures with the highest level of stability and lowest cost, as well as the prevention of faulty risk, is the desired plan that stakeholders seek to obtain.